Interactive biomechanics and elctronic textiles - Helmer, R.; Blanchonette, I.; Farrow, D.; Baker, J.; Phillips, E. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This paper presents an overview of a wearable interactive system developed by CSIRO that uses electronic textiles to enable interactive biomechanical measurement and feedback. Textile strain sensors are used to measure limb motion with real-time data streaming and analysis that enables interactive feedback to assist with skill acquisition. The system can be used in diverse training and competition environments, as illustrated via examples in kicking, throwing and paddling.